Activation of the LRR Receptor-Like Kinase PSY1R Requires Transphosphorylation of Residues in the Activation Loop - Oehlenschlæger, Christian B.; Gersby, Lotte B. A.; Ahsan, Nagib; Pedersen, Jesper T.; Kristensen, Astrid; Solakova, Tsvetelina V.; Thelen, Jay J.; Fuglsang, Anja T. (Frontiers in Plant Science, 2017)
PSY1R is a leucine-rich repeat (LRR) receptor-like kinase previously shown to act as receptor for the plant peptide hormone PSY1 and to regulate cell expansion. PSY1R phosphorylates and thereby regulates the activity of plasma membrane-localized H+-ATPases. While this mechanism has been studied in detail, little is known about how PSY1R itself is activated. Here we studied the activation mechanism of PSY1R. We show that full-length PSY1R interacts with members of the SERK co-receptor family in planta. We identified seven in vitro autophosphorylation sites on serine and threonine residues within the kinase domain of PSY1R using mass spectrometry. We furthermore show that PSY1R autophosphorylation occurs in trans and that the initial transphosphorylation takes place within the activation loop at residues Ser951, Thr959, and Thr963. While Thr959 and Thr963 are conserved among other related plant LRR RLKs, Ser951 is unique to PSY1R. Based on homology modeling we propose that phosphorylation of Ser951 stabilize the inactive conformation of PSY1R.